Mineralized Peyronie's plaque has a phenotypic resemblance to bone. (1st March 2022) - Ustriyana, Putu; Hennefarth, Matthew R.; Srirangapatanam, Sudarshan; Jung, Haeyoon; Wang, Yongmei; Chen, Ling; Lue, Tom F.; Lin, Guiting; Kang, Misun; Stoller, Marshall L.; Ho, Sunita P.
Abstract: Mineralized Peyronie's plaque (MPP) impairs penile function. The association, colocalization, and dynamic interplay between organic and inorganic constituents can provide insights into biomineralization of Peyronie's plaque. Human MPPs ( n  = 11) were surgically excised, and the organic and inorganic constituents were spatially mapped using multiple high-resolution imaging techniques. Multiscale image analyses resulted in spatial colocalization of elements within a highly porous material with heterogenous composition, lamellae, and osteocytic lacuna-like features with a morphological resemblance to bone. The lower (520 ± 179 mg/cc) and higher (1024 ± 155 mg/cc) mineral density regions were associated with higher (11%) and lower (7%) porosities in MPP. Energy dispersive X-ray and micro-X-ray fluorescent spectroscopic maps in the higher mineral density regions of MPP revealed higher counts of calcium (Ca) and phosphorus (P), and a Ca/P ratio of 1.48 ± 0.06 similar to bone. More importantly, higher counts of zinc (Zn) were localized at the interface between softer (more organic to inorganic ratio) and harder (less organic to inorganic ratio) tissue regions of MPP and adjacent softer matrix, indicating the involvement of Zn-related proteins and/or pathways in the formation of MPP. In particular, dentin matrix protein-1 (DMP-1) was colocalized in a matrix rich in proteoglycans and collagen that contained osteocytic lacuna-like features. This combined materials science and biochemical with correlative microspectroscopic approach provided insights into the plausible cellular and biochemical pathways that incite mineralization of an existing fibrous Peyronie's plaque. Statement of significance: Aberrant human penile mineralization is known as mineralized Peyronie's plaque (MPP) and often results in a loss of form and function. This study focuses on investigating the spatial association of matrix proteins and elemental composition of MPP by colocalizing calcium, phosphorus, and trace metal zinc with dentin matrix protein 1 (DMP-1), acidic proteoglycans, and fibrillar collagen along with the cellular components using high resolution correlative microspectroscopy techniques. Spatial maps provided insights into cellular and biochemical pathways that incite mineralization of fibrous Peyronie's plaque in humans. Graphical abstract: Image, graphical abstract